(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the functional outcome of limited fasciectomy for the treatment of Dupuytren’s contracture. Methods: This descriptive study was conducted in District Head Quarter Hospital Timergara Khyber Pakhtunkhwa and Khyber Teaching Hospital Peshawar from 21st March 2018 to 21st March 2021. All patients of Dupuytren’s contracture fulfilling the inclusion criteria were treated with limited fasciectomy (LF). Post operative functional outcome was assessed with Khan and Iqbal criteria and graded as excellent, good, fair and poor. Results: In this study 12 patients (20 hands) were included. All patients were male. The mean age was 61.5± 7 years. The mean duration of follow up was 14.4±3(range 12 to 16 months). Excellent outcome was reported in 14(70%) hands, good in 5(25%) and fair in 1(5%) hand. No intra operative or post operative complications were noted. We reported recurrence in one hand. Conclusion: Excellent functional outcome was achieved with limited fasciectomy in patients with Dupuytren’s contracture in our series. We recommend limited fasciectomy as the technique of choice to treat Dupuytren’s contracture.